An assessment of women's knowledge and attitude to environmental information in Nigeria (1998)
This paper discussed the level of awareness the Nigerian women should have about the enviroment and how important it is to a nation. Some selected group of women traders and female students were studied. The study discovers that formal education have a role to play on how people get environmental information in that the female students seems to have more knowledge about the environmnet that their trader counterparts. Environmental agencies should intensify their efforts by engaging in environmental enlightenment activities, like public lectures that will cut across all sectors of the society i.e the educated and uneducated, urban and rural. Electronic media houses should produce more jingles/adverts to be aired at all times. The federal office of statistics should carry out yearly or monthly survey to determine how environmental information benefits the populace. In other words, the enlightenment of women on environmental issues should be taken serious.